THE UNCONSTITUTIONAL ENVIRONMENTAL STATE OF AFFAIRS: CONSIDERATIONS ON ADPF 760-DF (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article analyzes the declaration by the Federal Supreme Court of an Unconstitutional Environmental State of Affairs due to the institutional dismantling of environmental protection bodies and mechanisms in Brazil. In the judgment of the Claim of Non-Compliance with Fundamental Precepts (ADPF) No. 760-DF, the Supreme Court understood that there is an unconstitutional state of affairs in environmental matters, requiring measures of a structural nature, considering that art. 225 of the Federal Constitution enshrines everyone's right to an ecologically balanced environment, giving the Public Power the duty to defend and preserve it for present and future generations. In addition to constituting a fundamental right in itself, a healthy environment is internationally recognized as a prerequisite for the enjoyment of other rights that are part of the existential minimum, in such a way that environmental protection is not a political option, but a constitutional duty, which, once again, it reinforces the legitimacy of judicial action. For the development of the work, bibliographical and documentary research was carried out, with a qualitative approach, whose data collected were analyzed based on the application of hypothetical-deductive and inductive methods.